The Global Burden of Diseases attributed to high low-density lipoprotein cholesterol from 1990 to 2019 - Zheng, Jia; Wang, Jing; Zhang, Yan; Xia, Jiangliu; Guo, Huilan; Hu, Haiying; Shan, Pengfei; Li, Tianlang (Frontiers in Public Health, 2022)
Background: To demonstrate the real-word situation of burdens that are attributed to the risk factor of high low-density lipoprotein cholesterol (LDL-C) at the global, regional, national levels, among different age groups and between genders. Methods: High-quality data were obtained in the Global Burden of Disease study which includes measures like deaths, disability-adjusted life years (DALYs), summary exposure value (SEV), average annual percentage change (AAPC) and observed to expected ratios (O/E ratios), Results: Globally, in 2019 deaths and DALYs attributed to high LDL cholesterol were 1.47 and 1.41times higher than that in 1990. The age-standardized deaths and DALYs rate was 1.45 and 1.70 times in males compared to females, the age-standardized SEVs rate was 1.10 times in females compared to males. The deaths, DALYs and SEVs rates increased with age. In 2019, the highest age-standardized rates of both deaths and DALYs occurred in Eastern Europe while the lowest occurred in high-income Asia pacific. The High-income North America experienced dramatic reduction of risk related to high LDL-C. Correlation analysis identified that the age-standardized SEVs rate was positively correlated with Socio-demographic Index (SDI) (P<0.001). The average annual percentage change (AAPC) of age-standardized SEVs rate decreased in the high SDI and high-middle SDI regions but increased in the middle SDI, low-middle SDI and low SDI regions. High LDL-C mainly contributed to ischemic heart diseases. Conclusion: High LDL-C contributed great amount of health burden worldwide. The males suffered worse health outcomes attributed to high LDL-C when compared to the females. The burden attributed to high LDL-C increased with age. Lower SDI regions and countries were experiencing more challenge of health problems attributed to high LDL-C as the progress of social development and should gain more policy preference.